2021
DOI: 10.1021/acs.jafc.1c05274
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Surface-Enhanced Raman Scattering-Based Aptasensors for Food Safety Detection

Abstract: Owing to the excellent performances of high sensitivity, high specificity, on-site detection, and multiplexing capability, surface-enhanced Raman scattering (SERS)-based aptasensors have performed prosperous applications and gained impressive progress in food safety. Herein, we reviewed the SERS-based aptasensors from the principles to specific applications in food safety. First, the sensor-working principles, SERS label design and preparation are introduced. Then, the popular platforms in the aptasensors are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 105 publications
(203 reference statements)
0
13
0
Order By: Relevance
“…Molecules can be combined with SERS tags to form an immunocomplex whose structure disintegrates and releases Raman probes, causing signal alterations 121 . Similarly, SERS-based aptasensors have significantly progressed in the area of food safety 122 . To monitor medicine distribution and support PTT and PDT, the NP-Raman combination (manifested through SERS) may be combined with various theranostic techniques ( Figure 5 A ) 123 .…”
Section: Raman Probes For Theranosticsmentioning
confidence: 99%
“…Molecules can be combined with SERS tags to form an immunocomplex whose structure disintegrates and releases Raman probes, causing signal alterations 121 . Similarly, SERS-based aptasensors have significantly progressed in the area of food safety 122 . To monitor medicine distribution and support PTT and PDT, the NP-Raman combination (manifested through SERS) may be combined with various theranostic techniques ( Figure 5 A ) 123 .…”
Section: Raman Probes For Theranosticsmentioning
confidence: 99%
“…The rapid detection sensors for food toxins developed with MOFs are mainly based on three fundamental principles: (i) quenching luminous groups of MOFs such as the fluorescence and ultraviolet caused by the conjugated pi groups of ligands and lanthanide ion clusters ( Nong et al, 2020 ) (ii) capturing guest molecules by activated groups of MOFs or encapsulated constituents with further reactions (redox reaction and chromogenic reaction) and (iii) enhancing the spectral signals of target analytes located close to the plasmonic nanoparticles or nanostructured surfaces ( Yan et al, 2021 ; Chio et al, 2022 ). Therefore, the MOFs-based sensors employed in detecting food toxins can be divided into luminescent, electrochemical, colorimetric, and SERS sensors.…”
Section: Applications and Mechanisms Of Mofs-based Sensors In Toxins ...mentioning
confidence: 99%
“…1 Since the discovery of surface-enhanced Raman spectroscopy (SERS) over 40 years ago, 2 it has undergone a steady growth in interest from the research community. At present, it is widely applied in various fields, such as electrochemistry, 3 biology, 4 the prediction of disease, 5 food safety 6 and materials science. 7 Research has shown that the SERS effect is dependent on the use of SERS substrates.…”
Section: Introductionmentioning
confidence: 99%